Infrastructure Financing Through Islamic Sukuk: Case Studies in Malaysia Le Financement d'Infrastructures par les Sukuk Islamiques : Études de Cas en Mala1isie - MEDANI, Ahmed (Finance and Business Economies Review, 2019)
This paper examines the prominent role of sukuk in financing infrastructure investments in Malaysia by addressing the reality of the global infrastructure market, the reality and performance of the sukuk market and its contribution to financing infrastructure investments in general and in Malaysia in particular, through a presentation of three leading models are: DanaInfra Retail Sukuk, Khazanah Ihsan Sukuk and Green SRI Sukuk Tadau.